Semantik Bahasa Indonesia: Kajian Makna Kata dan Struktur Makna - Suci Hasanah; Silvina Noviyanti; Anggi Sylvia; Fenny watini; Dewi Nurasyifa; Maria Valerina Br. Siboro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine word meaning (lexical semantics) and meaning structure (structural semantics) in the Indonesian language using a literature review approach. Data were collected from nationally accredited and SINTA-indexed scholarly articles retrieved from Google Scholar using relevant keywords on Indonesian semantics. The findings indicate that lexical semantics refers to the basic meaning inherent in a lexeme independently, which is relatively stable and can be found in dictionaries, such as the intrinsic meaning of words like “kuda” (horse) or “kursi” (chair). In contrast, structural meaning emerges from grammatical relationships between language elements in sentences or phrases, making it compositional and highly influenced by context and syntactic arrangement. These two dimensions of meaning complement each other; lexical meaning provides the foundation, while structural meaning offers flexibility and interpretive depth. Understanding both has significant implications for Indonesian language teaching, literary analysis, and the development of natural language processing technology. This study concludes that the semantic system of Indonesian is systematic and dynamic, capable of reflecting thoughts, culture, and social changes in Nusantara society. Keywords: Indonesian semantics, lexical meaning, structural meaning, structural semantics, grammatical meaning, literature review